Population data collection as an instrument for preventing social conflict: a study in Gampong Meurandeh Dayah - Ramadani, Siti; Aldino, Hanri; Rachmad, Andi; Krisna, Liza Agnesta Krisna; Fachrizal, Fachrizal (Jurnal Geuthèë: Penelitian Multidisiplin, 2025)
This study aims to examine the strategic role of population data collection by the village government as an instrument for preventing social conflict between local residents and migrants in Gampong Meurandeh Dayah, Langsa City. Employing a juridical-empirical method through field studies, data were collected via interviews, observations, and documentation involving village officials and community members. The findings reveal that the increasing number of migrant residents—primarily students from outside the region—has led to potential social frictions stemming from cultural differences and weak administrative oversight. The village government implements various data collection mechanisms such as routine censuses, the use of the SIGAP village information system, and mandatory self-reporting by newcomers to obtain a domicile certificate. Accurate data collection has proven effective in the early identification of potential conflicts, regulating the number of migrants, and mapping social needs. Furthermore, approaches such as deliberation, the application of local wisdom, and customary-based mediation have served as effective conflict resolution tools. This study underscores that systematic and collaborative population registration is crucial in fostering social harmony at the village level.